Tradisi Nikah Malem Songo di Tuban Jawa Timur : Studi Living Hadis - Evi Dwi Intan Mey Prafita; Rikhlatul Qurba; Kholila Mukaromah (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This article aims to reveal the meaning of marriage during the ninth night of Ramadhan, especially in Tuban Regency. This tradition is highly esteemed among the people of Tuban and has been passed down through generations.